Temporalities and resistance(s): historical analysis of the original peoples of Acre (Brazil): Temporalidades e resistência(s): uma análise histórica dos povos originários do/no Acre (Brasil) (Revista de História da UEG (REVHIST), 2024)
This article examines the history of the indigenous peoples of Acre, delving into a periodization that spans from pre-colonial times to the 21st century. It outlines five distinct phases: the Time of Malocas, the Time of Raids, the Time of Captivity, the Time of Rights, and the Time of Indigenous Governance or the Time of Contemporary History. This periodization reveals the complexity of socio-cultural and political interactions between indigenous and non-indigenous peoples. Rooted in a collaboration between the indigenous movements of Acre and the Pro-Indian Commission of Acre (CPI-AC), the study challenges linear historical narratives, advocating for a reinterpretation of historical events from indigenous perspectives. It highlights the indigenous peoples' resistance in the face of colonization, economic exploitation, and state policies, underlining the role of strategic alliances in the battle for territorial and cultural rights. This article contributes to the decolonization of regional historiography, aiming for a more equitable understanding of the historical experiences of Acre's original inhabitants and urging action to ensure their rights and dignity.Keywords: Indigenous History. Acre. Indigenous Peoples. Temporality.